German Modal Particles as Discourse Signals - Seemann, Hannah; Scheffler, Tatjana (Dialogue and discourse, 2025)
This study investigates the interaction of German modal particles like ja and doch with discourse structure. We conduct an acceptability study of modal particles in four discourse relations (CIRCUMSTANCE, CONDITION, EVIDENCE, JUSTIFY) to test predictions of (in)compatibilities derived from a corpus study by Döring and Repp (2019). As ratings for sentences representing the discourse relations CIRCUMSTANCE and CONDITION were significantly lower than for the two causal relations if presented with a modal particle, we confirm that modal particles and discourse structure interact. In a forced-choice study testing the particle ja's effect on relation disambiguation, we show that ja supports a causal interpretation of an ambiguous context in the absence of explicit discourse markers. Our findings contribute to delineating the role of German modal particles in discourse, as we show that there is an interaction between discourse relations and modal particles, meaning that readers do not accept all modal particles in every discourse relation, and at least the modal particle ja serves as a non-connective discourse signal for causal relations.